Cardiovascular disease, diabetes and established risk factors among populations of sub-Saharan African descent in Europe: a literature review - de Graft Aikins Ama; Bhopal Raj; Addo Juliet; Agyemang Charles; Stronks Karien (BMC, 2009)
Abstract Background Most European countries are ethnically and culturally diverse. Globally, cardiovascular disease (CVD) is the leading cause of death. The major risk factors for CVD have been well established. This picture holds true for all regions of the world and in different ethnic groups. However, the prevalence of CVD and related risk factors vary among ethnic groups. Methods This article provides a review of current understanding of the epidemiology of vascular disease, principally coronary heart disease (CHD), stroke and related risk factors among populations of Sub-Sahara African descent (henceforth, African descent) in comparison with the European populations in Europe. Results Compared with European populations, populations of African descent have an increased risk of stroke, whereas CHD is less common. They also have higher rates of hypertension and diabetes than European populations. Obesity is highly prevalent, but smoking rate is lower among African descent women. Older people of African descent have more favourable lipid profile and dietary habits than their European counterparts. Alcohol consumption is less common among populations of African descent. The rate of physical activity differs between European countries. Dutch African-Suriname men and women are less physically active than the White-Dutch whereas British African women are more physically active than women in the general population. Literature on psychosocial stress shows inconsistent results. Conclusion Hypertension and diabetes are highly prevalent among African populations, which may explain their high rate of stroke in Europe. The relatively low rate of CHD may be explained by the low rates of other risk factors including a more favourable lipid profile and the low prevalence of smoking. The risk factors are changing, and on the whole, getting worse especially among African women. Cohort studies and clinical trials are therefore needed among these groups to determine the relative contribution of vascular risk factors, and to help guide the prevention efforts. There is a clear need for intervention studies among these populations in Europe.